Uniaxial stress relaxation measurement in fluoroindate glasses - Filho, Barros D.A.; Ferraz, A. Machado; Messaddeq, Younes [UNESP]; Aegerter, M. A. (Elsevier, 1997)
Glasses of composition 40InF3-20SrF2-16BaF2-20ZnF 2-2GdF3-2NaF (mol%) have been prepared under controlled atmosphere. The time response of the stresses under the application of a constant strain was determined by microellipsometer technique, performed in ambient atmosphere at T < Tg = 294°C. The glasses show a Newtonian behavior at small stress level. During the relaxation process, very small grooves perpendicular to the applied strain appeared on the glass surface and affected its behavior after a time. The formation of these grooves is associated with the ambient atmosphere. Measurements in dry atmosphere showed that humidity was an important parameter in the relaxation process.
Keywords: Atmospheric humidity; Composition; Ellipsometry; Indium compounds; Mechanical variables measurement; Molecules; Newtonian flow; Oxides; Strain; Stress relaxation; Thermal effects; Water; Dilation; Fluoroindate glasses; Grooves; Microellipsometer technique; Stress relaxation measurement; Optical glass